MHealth: An updated systematic review with a focus on HIV/AIDS and tuberculosis long term management using mobile phones. Issue 2 (November 2015) - Devi, Balla Rama; Syed-Abdul, Shabbir; Kumar, Arun; Iqbal, Usman; Nguyen, Phung-Anh; Li, Yu-Chuan (Jack); Jian, Wen-Shan
Abstract Objective To evaluate the utilization of mobile phone technology for treatment adherence, prevention, education, data collection, monitoring long-term management of HIV/AIDS and TB patients. Methods Articles published in English language from January 2005 until now from PubMed/MEDLINE, EMBASE, Web of Science, WHO databases, and clinical trials were included. Data extraction is based on medication adherence, quality of care, prevention, education, motivation for HIV test, data collection from HIV lab test results and patient monitoring. Articles selected for the analysis cover RCTs and non RCTs related to the use of mobile phones for long-term care and treatment of HIV/AIDS and TB patients. Results Out of 90 articles selected for the analysis, a large number of studies, 44 (49%) were conducted in developing countries, 24 (26%) studies from developed countries, 12 (13%) are systematic reviews and 10 (11%) did not mention study location. Forty seven (52.2%) articles focused on treatment, 11 (12.2%) on quality of care, 8 (9%) on prevention, 13 (14.4%) on education, 6 (6.6%) on data collection, and 5 (5.5%) on patient monitoring. Overall, 66 (73%) articles reported positive effects, 21 (23%) were neutral and 3 (4%) reported negative results. Conclusions Mobile phone technology is widely reported to be an effective tool for HIV/AIDS and TB long-term care. It can substantially reduce disease burden on health care systems by rendering more efficient prevention, treatment, education, data collection and management support.